Florida’s Seepage Slope Wetlands - Megan E. Brown; Debbie L. Miller (EDIS, 2012)
Florida is home to one of North America’s most unique and diverse ecosystems, the seepage slope. Unusual hydrology and frequent fires combine to create an environment that supports a variety of carnivorous and other sun-loving herbaceous plants. This 5-page fact sheet discusses the natural history and conservation concerns associated with seepage slope wetlands. Written by Megan E. Brown and Debbie L. Miller, and published by the UF Department of Wildlife Ecology and Conservation, June 2012.